Contamination of Bathing Waters with Trihalomethanes in Slovenia - Darko - Drev; Aleksandra Krivograd Klemenčič; Janez Škarja; Jože Panjan (Zdravniški Vestnik, 2015)
THM and AOX compounds form as by-products of disinfection with the use of chlorine. THM compounds can pose problems for pool water, while AOX compounds can be problematic for waste water. Today's state of the art technology allows for proper removal of THM and AOX compounds from water. In addition, new disinfection technologies are currently being developed that will significantly reduce the use of chlorine and thus the formation of THM and AOX compounds.